Use of electronic resources by the undergraduate students of Mapua Institute of Technology, Makati Campus - Tavora, Hazel Anne B. (School of Library and Information Studies, University of the Philippines Diliman, 2012)
The purpose of this study is to determine use of electronic resources by the undergraduate students of Mapua Institute of Technology, Makati Campus mainly to (1) Find out the frequency of use of the electronic resources by the undergraduate students (2) Determine the factors that the undergraduate students consider in searching information from electronic resources and to (3) Identify how the undergraduate students seek information from the electronic resources.